2013
DOI: 10.1371/journal.pone.0069399
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Mathematical Study and the Development of Conditional Reasoning Skills

Abstract: Since the time of Plato, philosophers and educational policy-makers have assumed that the study of mathematics improves one's general ‘thinking skills’. Today, this argument, known as the ‘Theory of Formal Discipline’ is used in policy debates to prioritize mathematics in school curricula. But there is no strong research evidence which justifies it. We tested the Theory of Formal Discipline by tracking the development of conditional reasoning behavior in students studying post-compulsory mathematics compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
46
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 31 publications
(42 reference statements)
7
46
2
1
Order By: Relevance
“…However, it should be noted that the change Attridge and Inglis (2013) observed was not quite as the TFD would predict. Proponents of the TFD suggest that mathematics teaches students to reason with 'logic', implying that their reasoning should become more normative.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…However, it should be noted that the change Attridge and Inglis (2013) observed was not quite as the TFD would predict. Proponents of the TFD suggest that mathematics teaches students to reason with 'logic', implying that their reasoning should become more normative.…”
mentioning
confidence: 68%
“…They argued that studying mathematics at A level (a non-compulsory qualification taken at the ages of 16-18 in England and Wales) may have been responsible for the initial difference between groups. This was supported by Attridge and Inglis (2013) who studied abstract conditional reasoning skills in mathematics and literature A level students, and found no difference between groups in reasoning behaviour at the start of post-compulsory education. While the literature students' reasoning did not change during their first year of undergraduate studies, the mathematics students' did.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Previous research has established a bidirectional relationship between mathematics and logical reasoning skills. For example, Attridge and Inglis, (2013) found that education in mathematics improved logical reasoning skills, and Morsanyi, Devine, Nobes, and Szücs (2013) found that children with superior mathematical abilities excelled in logical reasoning.…”
Section: Intelligence and Logical Reasoningmentioning
confidence: 99%